The effect of the length, angle, height, and depth of lumbar lordosis on selected features of thoracic spine - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2023)
The purpose of this study was to demonstrate the significant effect of the values of the angle, depth, height, and length of lumbar lordosis on selected features of the thoracic spine. Material and Methods. The study was carried out in a group of 2,361 children aged 7 to 15 years, in 6 semiannual consecutive editions. This allowed to record 16,608 observations of 31 features describing posture by photogrammetric method. Results. The following influential features like angle, depth, heights, and lengths of lumbar lordosis were selected for multiple regression analysis with selection of a subset of the optimal set of variables. Conclusions The presented statistical analysis shows the mutual influence of the values of the selected characteristics. The study showed no independent feature, however, the degree of influence varied. This demonstrates the interrelatedness of the different spinal segments. Corrective actions that change the value of one postural trait force the change of others in a positive or negative way.